(NrEWOL@CIONNOE DWIVENIE W rOSSII WO WTOROJ ^ETWERTI (BXIX (NW(B. :s ((NrEWOL@CIONNYE ORGANIZACII I KRUVKI(B) /s - (NfEDOSOW(B, (NiWAN aNTONOWI^s ((NmOSKW(Ba :s (NsOC\KGIZ(B,s, 1958)
(NzAKL(B.: (NS(B. 375-382s
(NlIT(B.: (NS(B. 382-414s
Keywords: (NiSTORIQs